EVALUATION OF THE PHYSICO-CHEMICAL AND ORGANOLEPTIC PROPERTIES OF TEMPE DERIVED FROM VARIOUS OF SOYBEAN VARIETY - Nikmatul Hidayah; Resa Setia Adiandri; Mary Astuti (Widyariset, 2012)
Imported soybean as raw material for making tempe was preferred than local soybean due to better qualities in colour and uniform seed size. This study was carried out to evaluate the physical, chemical and organoleptic properties of tempe derived from both local and imported soybean. Five local soybean varieties and an imported soybean were examined in this research. This study consisted of two steps: (1) making of the tempe from various of soybean variety; (2) characterizing the tempe such as the physical properties (density, texture, pH, yield), chemical properties (water content, ash content, protein, fat, carbohydrate), and organoleptic properties (colour, smell, flavour, preference). The result showed that tempe derived from local soybean had a better quality than imported soybean tempe for its physical, chemical and organoleptic properties. Galunggung tempe had the highest yield and Anjasmara tempe had the highest protein content. Based on organoleptic properties, it shows that Bromo tempe had the highest preference value.